Adaptive QoS control of DSRC vehicle networks for collaborative vehicle safety applications. - Wenyang Guan (2013)
Road traffic safety has been a subject of worldwide concern. Dedicated short range communications (DSRC) is widely regarded as a promising enabling technology for collaborative safety applications (CSA), which can provide robust communication and affordable performance to build large scale CSA system. The main focus of this thesis is to develop solutions for DSRC QoS control in order to provide robust QoS support for CSA. The first design objective is to ensure robust and reliable message delivery services for safety applications from the DSRC networks. As the spectrum resources allocated to DSRC network are expected to be shared by both safety and non-safety applications, the second design objective is to make QoS control schemes bandwidth-efficient in order to leave as much as possible bandwidth for non-safety applications. The first part of the thesis investigates QoS control in infrastructure based DSRC networks, where roadside access points (AP) are available to control QoS control at road intersections. After analyse DSRC network capabilities on QoS provisioning without congestion control, we propose a two-phases adaptive QoS control method for DSRC vehicle networks. In the first phase an offline simulation based approach is used to and out the best possible system configurations (e.g. message rate and transmit power) with given numbers of vehicles and QoS requirements. It is noted that with different utility functions the values of optimal parameters proposed by the two phases centralized QoS control scheme will be different. The conclusions obtained with the proposed scheme are dependent on the chosen utility functions. But the proposed two phases centralized QoS control scheme is general and is applicable to different utility functions. In the second phase, these configurations are used online by roadside AP adaptively according to dynamic traffic loads. The second part of the thesis is focused on distributed QoS control for DSRC networks. A framework of collaborative QoS control is proposed, following which we utilize the local channel busy time as the indicator of network congestion and adaptively adjust safety message rate by a modified additive increase and multiplicative decrease (AIMD) method in a distributed way. Numerical results demonstrate the effectiveness of the proposed QoS control schemes.